2012
DOI: 10.5194/nhess-12-805-2012
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the temporal fluctuations of the reservoir-triggered seismicity observed at Açu (Brazil)

Abstract: <p><strong>Abstract.</strong> The time dynamics of the reservoir-induced seismicity observed in Açu area (Brazil) from November 1994 to April 1997 reveals a super-Poissonian behaviour in the direction of a clustering process, where the occurrence of an earthquake increases the likelihood of the occurrence of a subsequent one. The seismicity shows strong correlation for time scales larger than approximately 1 day up to about four months, being characterized by Poissonian behavior for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Thus, the hydraulic diffusivity along the Jiali Fault influences the speed of the evolution of seismic activity (see Hainzl, 2004 for more explanation). As proposed by Telesca et al (2012) in reservoir-triggered seismicity observed at Acu, Brazil, we also conclude that the processes of formation of fractures in the anisotropic and heterogeneous rockmass, along with pore pressure diffusion driven processes, are hypothesized as physical mechanisms for swarm generation in the study area.…”
Section: Whether Pore Pressure Is Responsible For Swarm Generation?mentioning
confidence: 76%
“…Thus, the hydraulic diffusivity along the Jiali Fault influences the speed of the evolution of seismic activity (see Hainzl, 2004 for more explanation). As proposed by Telesca et al (2012) in reservoir-triggered seismicity observed at Acu, Brazil, we also conclude that the processes of formation of fractures in the anisotropic and heterogeneous rockmass, along with pore pressure diffusion driven processes, are hypothesized as physical mechanisms for swarm generation in the study area.…”
Section: Whether Pore Pressure Is Responsible For Swarm Generation?mentioning
confidence: 76%
“…Field observations and scientific research from the two last decades provide arguments that are in favor of reservoir-induced seismicity (Talwani, 1997;Peinke et al, 2006;Telesca, 2010Telesca, , 2011Telesca et al, 2012a). The strength of such reservoir-triggered earthquakes was found to be in the range from damaging earthquakes (Talwani, 1997) to micro-seismic emissions (Chander and Sarkar, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…(Snaebjörnsson, et al 2006;Sigtryggsdóttir et al 2013b) TM Reservoirs may trigger RTEs. (Gupta 2002;Telesca et al 2012;ICOLD 2011) Reservoir (Res) (Gráková et al, 2007) ) IW (Muço, 2013 Pandey and Chadha (2003), Mekkawi (2004), Gupta (2002) d Def is abbreviation for deformation Nat Hazards (2003) …”
Section: Appendixmentioning
confidence: 99%
“…Rajendran et al (2013),Telesca et al (2012), Ferreira et al (2008,Gahalaut et al (2007),Peinke et al (2006), Do,Lunn et al (2004),Gupta (2001) bItaba (2008),Chadha et al (2008),Singh et al (2008). Alarm potential(Reddy and Nagabhushanam 2011;Yuce et al 2010;Zhang et al 2013a) cGupta (2013),…”
mentioning
confidence: 96%